Heart of Darkness : An Authoritative Text, Backgrounds and Sources, Essays in Criticism - Conrad, Joseph; Edited by Robert Kimbrough (New York Norton & Company, 1963)
In turn-of-the century Africa, colonial traders driven by greed brave forbidding dangers to exploit the continent's vast treasures. One of these is sea captain Marlow, who penetrates the Congo's jungles in pursuit of the mysterious Mr. Kurtz, deranged chief of a remote trading station.
Include Bibliography
Keywords: Suffering -- Europeans -- Degeneration